Holocene fluvial history of the Nile's west bank at ancient Thebes, Luxor, Egypt, and its relation with cultural dynamics and basin‐wide hydroclimatic variability. Issue 3 (10th July 2017) - Toonen, Willem H. J.; Graham, Angus; Pennington, Benjamin T.; Hunter, Morag A.; Strutt, Kristian D.; Barker, Dominic S.; Masson‐Berghoff, Aurélia; Emery, Virginia L.
Abstract: In the Theban area around modern Luxor (Egypt), the River Nile divides the temple complexes of Karnak and Luxor from New Kingdom royal cult temples on the western desert edge. Few sites have been archaeologically identified in the western flood plain, despite its presumed pivotal role in the ancient ritual landscape as the territory that both physically divided and symbolically connected the areas inhabited by the living and the areas occupied by the dead. Using borehole data and electrical resistivity tomography, the current investigation of subsurface deposits reveals the location of an abandoned channel of the Nile. This river course was positioned in the western, distal part of the Nile flood plain. Over 2100 ceramic fragments recovered from boreholes date the abandonment of the relatively minor river channel to the (late) New Kingdom. This minor river branch could have played an important role in the cultural landscape, as it would have served to connect important localities in the ritual landscape. Changes in the fluvial landscape match with established periods of basin‐wide hydroclimatic variability. This links cultural and landscape changes observed on a regional scale to hydroclimatic dynamics in the larger Nile catchment, in one of the focal areas of Ancient Egyptian cultural development.